Towards a specific approach to education in dental ethics: a proposal for organising the topics of biomedical ethics for dental education - SERT, GÜRKAN; GÖRKEY, ŞEFİK (BMJ PUBLISHING GROUP, 2012)
Understanding dental ethics as a field separate from its much better known counterpart, medical ethics, is a relatively new, but necessary approach in bioethics. This need is particularly felt in dental education and establishing a curriculum specifically for dental ethics is a challenging task. Although certain topics such as informed consent and patient rights can be considered to be of equal importance in both fields, a number of ethical issues in dental practice are only remotelydif at alldrelevant for medical practice. Therefore, any sound approach to education in dental ethics has to recognise the unique aspects of dental practice in order to meet the needs of dental students and prepare them for the ethical challenges they may face during their professional practice. With this goal in mind, this paper examines the approach of the authors to dental ethics education and proposes a system to organise the topics of biomedical ethics for dental education. While the authors' perspective is based on their experience in Turkey, the proposed system of classification is not a rigid one; it is open to interpretation in other contexts with different social, cultural and professional expectations. Therefore, the paper also aims to inspire discussion on the development of an ideal dental ethics curriculum at an international level.